Sequência de Ensino Investigativo sobre o tema " Radioatividade " por meio de Histórias em Quadrinhos - Francischeto, Rodrigo Tardin (2020)
This research project presents a playful and motivating pedagogical resource to improve learning performance, arousing students' interest in a topic of chemistry - radioactivity. It reports an experience of comics elaboration (HQ) as didactic strategy for